Correlation among Lens Opacities Classification System III grading, the 25-item National Eye Institute Visual Functioning Questionnaire, and Visual Function Index-14 for age-related cataract assessment - Wan, Yu (Int Ophthalmol, 2020)
PURPOSE: To evaluate the relationship between cataract types and subjective visual function among patients with age-related cataract. METHODS: This was a prospective, multicenter, 831 Chinese patient-based, cross-sectional study. Patients were administered the Visual Function Index-14 (VF-14) and the 25-item National Eye Institute Visual Functioning Questionnaire (NEI-VFQ-25) to evaluate their subjective visual function. Lens Opacities Classification System III (LOCS III) was used to evaluate the type of cataract. Relationships among these parameters were analyzed. RESULTS: LOCS III cortical (C) and posterior subcapsular scores are negatively associated with VF-14 (r = − 0.188, P < 0.01; r = − 0.146, P < 0.01) and total score of NEI-VFQ-25 (r = − 0.223, P < 0.01; r = − 0.160, P < 0.01), respectively; LOCS III nuclear opalescence (NO) score is positively associated with VF-14 (r = 0.087, P < 0.05) and total score of NEI-VFQ-25 (r = 0.097, P < 0.05). In multiple linear regression, a decrease in the LOCS III C score is a significant predictor for improvement of the total score of NEI-VFQ-25 (β = − 1.286, P < 0.05). In contrast, an increase in LOCS III NO score is a significant predictor for improvement of VF-14 (β = 3.826, P < 0.01) and total score of NEI-VFQ-25 (β = 4.618, P < 0.01). Patients with LOCS III C score ≤ 2 have higher VF-14 (49.38 versus 43.74, P < 0.01), total (80.73 versus 71.58, P < 0.01) and subscale scores of NEI-VFQ-25 than patients with LOCS III C score > 2. CONCLUSION: Cortical cataract has adverse effects on subjective visual function, while mild-to-moderate nuclear cataract has positive effects. Furthermore, “LOCS III C score > 2” can be a potential cutoff as a reference for cataract surgery without self-assessing questionnaires. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10792-020-01353-0) contains supplementary material, which is available to authorized users.